Factors associated with early fully immunized status among indonesian children 9-12 months of age - Wahyono, Tri Yunis Miko
This case-control study aimed to determine if birth attendant, urban/rural place of residence and number of children under five years of age in the household were associated with the early fully immunized status of Indonesian children 9-12 months of age. Secondary data from the Indonesia National Socio-Economics Survey 1996 (SUSENAS 1996) were used. All 1,611 fully immunized children in the target age group were included as cases. Controls were 1,924 children who were not fully immunized. They were selected by stratified random sampling according to island group among those who were not fully immunized. The 6 island groups served as the stratification variable for control selection. Both cases and controls possessed immunization cards.In the final logistic regression model, the medical birth attendance was found to be associated with the early fully immunized status of children aged 9-12 months belonging to households with no other children under five years old. It also showed that children who were not fully immunized had greater tendencies to have been attended by non-medical birth attendants such as traditional birth attendants (TBAs). The number of children under five years old in the household was likewise shown to be correlated with early fully immunized status among children delivered by medical birth attendants and it was found that the children who were early fully immunized had greater probabilities of living in households with one child under five years old compared to those who were not fully immunized. Urban/rural place of residence also showed significant association with the immunization status of the children where chindren who were early fully immunized had greater tendencies of living in urban areas compared with those who were not fully immunized.Based on the results, this study recommends the need to strengthen the Family Planning and Maternal Child Health program through: training TBAs on immunization, prioritizing of rural areas for immunization program and intensifying family planning program.